1998
DOI: 10.1123/tsp.12.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the Individual Zones of Optimal Functioning Model for the Multimodal Treatment of Precompetitive Anxiety

Abstract: Effects of a precompetitive anxiety regulation system, based upon tenets of the individual zones of optimal functioning (IZOF) model, multidimensional anxiety theory, and the specific-effects hypothesis, were tested. In Phase I, case studies (3 elite adolescent tennis players) were used to analyze the IZOF model within a multidimensional state anxiety framework. In Phase II, the effectiveness of a precompetitive anxiety regulation system, based upon IZOF and the specific-effects hypothesis, was tested for enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Prediction of individual performance based on contrasts of precompetition emotional states with previously established IZOFs in multiple emotions received fairly good empirical support (Annesi, 1998;Hanin, , 2004Robazza, Pellizzari, & Hanin, 2004). In most cases, the optimal and dysfunctional zones were established using the focused recall procedures described earlier (Hanin, , 2003, 1996.…”
Section: Beyond Optimal Intensity Zonesmentioning
confidence: 86%
“…Prediction of individual performance based on contrasts of precompetition emotional states with previously established IZOFs in multiple emotions received fairly good empirical support (Annesi, 1998;Hanin, , 2004Robazza, Pellizzari, & Hanin, 2004). In most cases, the optimal and dysfunctional zones were established using the focused recall procedures described earlier (Hanin, , 2003, 1996.…”
Section: Beyond Optimal Intensity Zonesmentioning
confidence: 86%
“…We believe in the effectiveness of an intervention based on the results of this research, since previous studies, similar to this one, have succeeded in helping athletes achieve their previously calculated optimum performance zones. 17,25 It seems that the use of IZOF theory proposed by this research is a more individualized and holistic model for assessments and interventions in the area of applied sport psychology.…”
Section: Discussionmentioning
confidence: 91%
“…Many researchers of the IZOF theory used the State-Trait Anxiety Inventory (STAI), proposed by Spielberger, Gorsuch and Lushene, 15 which provides an anxiety-state score in a one-dimensional perspective for establishing the optimal performance zone. More recently, some studies have adapted the IZOF theory 16,17 and used the Competitive State Anxiety Inventory -2 (CSAI-2), extending the IZOF theory to a multidimensional perspective of anxiety. According to Annesi, 17 the separation of the anxiety state into three subscales (cognitive, somatic, and self-confidence) is considered advantageous for sports psychologist interventions, as they should apply specific treatment to modify only the variables which the athlete cannot regulate.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the major components for enhancing athletic performance are a clear understanding of the task and a precise prediction of the performance outcome, which are contingent on emotional states (Annesi, 1998;Gould & Udry, 1994;Hanin, 2000;Hardy, Jones, & Gould, 1996). As a result, researchers expressed a cultivated interest in the affect-performance linkage (Gould & Tuffy, 1996;Hanin, 2000;Lazarus, 2000;Raglin & Hanin, 2000;Robazza, Bortoli, Zadro, & Nougier, 1998).…”
Section: The Individual Zone Of Optimal Functioningmentioning
confidence: 97%